Promoting Parental Involvement in Students Education through LMS Application - Rheza Pratama; Lina; Muhammad Asril Arilaha (SAFE-Network, 2023)
The research aims to discover the aspects of parental involvement in children's education so that the school and education stakeholders are not only able to maintain the relationship with the parents but also to construct another effective communication medium. The parental involvement is considered one of the main important things for students’ academic achievement, moreover, the implementation of blended learning during the pandemic has already boosted parental involvement towards their children’s study activities. The research used a quantitative approach with surveys applied. The data was analyzed descriptively by utilizing central tendency (mean and median). Parental involvement was measured through nine components of the Parental Involvement Rating Scale (PIRS). Each of the components consisted of three questions with a scale of responses 0 (disagree) up to 2 (Agree). There were 202 random respondents having at least one child with school-aged. Overall, the highest components of parental involvement were indicated in Parental Attention, Parental Guidance, and Parental Influence while the lowest component was Parental Decision Making. Even though the analysis of the highest components considered three aspects of respondents’ demography LMS users or not, the children’s age, and the monthly income, it still did not show significant differences.